2021
DOI: 10.5539/ach.v13n1p8
|View full text |Cite
|
Sign up to set email alerts
|

Practice and Transmission of Batik in Wukirsari Village, Yogyakarta -Safeguarding Intangible Cultural Heritage in Indonesia-

Abstract: The target of this research is to figure out the state of practice and transmission of Batik, an Indonesian textile dyeing Intangible Cultural Heritage, and necessary angles for its conservation. Knowledge related to Batik is shared and transmitted in craftspeople communities in Wukirsari Village, which is one of Batik centers in Indonesia. What’s more, Batik cloth production organizations play an essential role in the transmission of Batik technique through creating job opportunities, establishing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…American scholar Sol believes that intangible cultural elements can tell the differences between the cultural essence of different regions [10], and Prus, after studying the development of villages and intangible cultural heritage, believes that they have a cultural background and are influenced by various elements such as geography, history, physics and socio-economics [11]. Other scholars have achieved fruitful research results in the fields of the concept, typology, conservation, and exploitation of ICH [12,13], with further research focusing on the exploitation of ICH tourism and ICH tourism experiences [14][15][16], while some scholars have further suggested that the regeneration and sustainable development of ICH should be considered and they shouldn't be over-commercialized [3]. In recent years, the relationship between the protection of ICH and the cultural rights of the masses has been mostly analyzed from the perspective of the history of ICH and social identity, and the role of inheritance education in the protection of ICH has been emphasized to explore deeper research [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…American scholar Sol believes that intangible cultural elements can tell the differences between the cultural essence of different regions [10], and Prus, after studying the development of villages and intangible cultural heritage, believes that they have a cultural background and are influenced by various elements such as geography, history, physics and socio-economics [11]. Other scholars have achieved fruitful research results in the fields of the concept, typology, conservation, and exploitation of ICH [12,13], with further research focusing on the exploitation of ICH tourism and ICH tourism experiences [14][15][16], while some scholars have further suggested that the regeneration and sustainable development of ICH should be considered and they shouldn't be over-commercialized [3]. In recent years, the relationship between the protection of ICH and the cultural rights of the masses has been mostly analyzed from the perspective of the history of ICH and social identity, and the role of inheritance education in the protection of ICH has been emphasized to explore deeper research [17,18].…”
Section: Introductionmentioning
confidence: 99%